Stemming the Tide of Opioid Addiction—Dramatic Reductions in Postoperative Opioid Requirements Through Preoperative Education and a Standardized Analgesic Regimen. Issue 3 (17th October 2019) - Sheldon, Rowan R; Weiss, Jessica B; Do, Woo S; Forte, Dominic M; Carter, Preston L; Eckert, Matthew J; Sohn, Vance Y
Abstract: Introduction: Surgery is a known gateway to opioid use that may result in long-term morbidity. Given the paucity of evidence regarding the appropriate amount of postoperative opioid analgesia and variable prescribing education, we investigated prescribing habits before and after institution of a multimodal postoperative pain management protocol. Materials and Methods: Laparoscopic appendectomies, laparoscopic cholecystectomies, inguinal hernia repairs, and umbilical hernia repairs performed at a tertiary military medical center from 01 October 2016 until 30 September 2017 were examined. Prescriptions provided at discharge, oral morphine equivalents (OME), repeat prescriptions, and demographic data were obtained. A pain management regimen emphasizing nonopioid analgesics was then formulated and implemented with patient education about expected postoperative outcomes. After implementation, procedures performed from 01 November 2017 until 28 February 2018 were then examined and analyzed. Additionally, a patient satisfaction survey was provided focusing on efficacy of postoperative pain control. Results: Preprotocol, 559 patients met inclusion criteria. About 97.5% were provided an opioid prescription, but prescriptions varied widely (256 OME, standard deviation [SD] 109). Acetaminophen was prescribed often (89.5%), but nonsteroidal anti-inflammatory drug (NSAID) prescriptions were rare (14.7%). About 6.1% of patients required repeat opioid prescriptions. After implementation, 181 patients met inclusion criteria. Initial opioid prescriptions decreased 69.8% (77 OME, SD 35; P  < 0.001), while repeat opioid prescriptions remained statistically unchanged (2.79%; P  = 0.122). Acetaminophen prescribing rose to 96.7% ( P  = 0.002), and NSAID utilization increased to 71.0% ( P  < 0.001). Postoperative survey data were obtained in 75 patients (41.9%). About 68% stated that they did not use all of the opioids prescribed and 81% endorsed excellent or good pain control throughout their postoperative course. Conclusions: Appropriate preoperative counseling and utilization of nonopioid analgesics can dramatically reduce opioid use while maintaining high patient satisfaction. Patient-reported data suggest that even greater reductions may be possible.